Desenvolvimento de um escâner automatizado para medição sequencial e caracterização espaço-temporal de materiais acústicos - Souza, Gabriel Guimaraes Azzuz Athayde de (2022)
This thesis presents the development of an automated scanner for measuring sequential impulsive responses, to be applied on the spatio-temporal characterization of materials, used in acoustic treatment. The system uses the same type of technology as 3D printers, with a base that moves an acoustic sensor along the x, y, and z-axis. The sensor displacement is accomplished with stepper motors, controlled by an Arduino processor. Thus, a set of M impulse responses are measured sequentially with a configured array. With the M spatially-distributed impulsive responses collected, it is possible to map the spatial information in the sound field to a set of L plane waves, by solving the inverse problem with Tikhonov regularization. The built system is flexible, and different experiments can be executed accurately. This study focuses on the in situ impedance measurement. Once one computes the complex amplitudes of the L plane waves, the sound field can be reconstructed in the vicinity of the array, which allows the estimation of the surface impedance of a sound absorber.